2021
DOI: 10.1007/s11255-021-02798-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic performance of clinical assessment tools following hip fracture in patients with chronic kidney disease

Abstract: Purpose People living with chronic kidney disease (CKD) are at a higher risk of hip fracture with an associated increased mortality risk compared to individuals without CKD. Our study aimed to evaluate the clinical assessment tools that best predict mortality risk following hip fracture for patients with CKD. Methods Patients with CKD G3b-5D admitted to Lancashire Teaching Hospitals NHS Foundation Trust, U.K. between June 2013 and Dec 2019 were included. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Almost in all of the studies, a physician assessed the CFS score (82.14%), in six cases it was assessed by a nurse (10.71%), in two cases alternatively by a physician or a nurse (3.57%), in one case by an occupational therapist (1.97%), and in one study the patients performed a CFS self-assessment (1.97%). In 10 studies (17.86%), in addition to the CFS, other frailty indexes were employed: the Fried frailty criteria ( 53 , 55 , 58 , 62 ), Sarcopenia ( 44 , 45 ), Frailty index ( 51 , 53 ), CKD Frailty Index Lab ( 67 ), Liver frailty index ( 55 ), PARTNER frailty scale ( 53 ), Derby frailty scale ( 51 , 52 ), and Acute frailty ( 51 , 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Almost in all of the studies, a physician assessed the CFS score (82.14%), in six cases it was assessed by a nurse (10.71%), in two cases alternatively by a physician or a nurse (3.57%), in one case by an occupational therapist (1.97%), and in one study the patients performed a CFS self-assessment (1.97%). In 10 studies (17.86%), in addition to the CFS, other frailty indexes were employed: the Fried frailty criteria ( 53 , 55 , 58 , 62 ), Sarcopenia ( 44 , 45 ), Frailty index ( 51 , 53 ), CKD Frailty Index Lab ( 67 ), Liver frailty index ( 55 ), PARTNER frailty scale ( 53 ), Derby frailty scale ( 51 , 52 ), and Acute frailty ( 51 , 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the studies were published from 1994 to 2022. Eleven studies were conducted in European countries [25][26][27][28][29][30][31][32][33][34][35], whereas the other studies were from the USA [14,[36][37][38][39], Japan [40][41][42], Taiwan [16,17], Canada [43], South Korea [44], and Turkey [45]. Additionally, 17 studies [13,14,16,17,[25][26][27][29][30][31]33,[35][36][37]40,44,46] were conducted in multicenter settings, and the number of participants considerably varied from 12 to 610,524.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The longest follow-up duration was five years, and the participants' mean age ranged from 39 to 82.3 years. Out of the 26 studies, 20 investigated the prognosis of patients with hip fractures [14,16,17,[27][28][29]31,32,[34][35][36][37][38][39][40][41][43][44][45][46], and two [30,42] examined the prognosis of patients with spine fractures, whereas four [25][26][27]37] assessed the prognosis of both hip and spine fractures. Nine studies reported the surgery status for hip or spine fracture [17,28,31,32,37,38,40,43,44].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple frailty screening tools have been evaluated in CKD populations and perform reasonably well [28][29][30][31][32]. Notably, the widely cited Clinical Frailty Scale (CFS) [21,33], a global 9-point scale that guides the clinical judgement of an individual's frailty status, has been shown to be associated with adverse outcomes in Australian, Canadian, Japanese, South Korean, and UK CKD populations [34][35][36][37][38][39][40][41][42][43][44]. A limitation of the CFS is that it relies on a healthcare professional to make a subjective assessment, albeit an informed one.…”
Section: Frailty Identification and Assessmentmentioning
confidence: 99%